Cortical Information Pathway of Below-Average and Average Young Hand-Writers: A Pilot Study - Khalid, P. I.; Abd Ghani, M. H.; Alik, R.; Harun, M.; Mat Safri, N. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
A great deal of study has been performed to figure out the reasons of poor handwriting. Cortical information pathway is one of the intrinsic factors that is worth considering in understanding this difficulty yet received less attention from researchers. Thus, this study was conducted to evaluate the differences in cortical information pathway between the average and below-average young hand-writers. Six pre-school children who were categorized by Handwriting Proficiency Screening Questionnaire (HPSQ) and Screen Writer as average hand-writers and four other children as below-average hand-writers were asked to trace three basic geometric shapes. Their brain signals while tracing the shapes were acquired using electroencephalograph. The information pathway was extracted from the electroencephalogram and analyzed using Partial Directed Coherence (PDC) method. The results showed that most of the below-average young handwriters had to plan their hand movement before tracing the shapes. On the other hand, average hand-writers just only needed to recall their related experience to trace the basic shapes. In conclusion, the differences observed in cortical information pathway between the below-average writers and the average writers are essential. This finding has opened up a new research area for understanding the difficulty experienced by the below-average hand-writers and planning appropriate intervention programs to match the children’s need.